Psychological analysis of Personality Self-actualization and Sociability correlations - S S Kudinov (Peoples' Friendship University of Russia (RUDN University), 2011)
The scientific credence to the personality self-actualization and sociability correlations is given in the article. Within the frame of system-defined research, different individual-typological peculiarities of sociability are highlighted and characterized and their comparative analysis with the personality self-actualization is conducted.